2014
DOI: 10.1155/2014/156060
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Bioactive Peptide from the Seeds of Benincasa hispida

Abstract: A designated bioactive peptide “Hispidalin” purified from the seeds of Benincasa hispida, which is a medicinal plant, belongs to Cucurbitaceae family. Purification was achieved by using a procedure consisting of extraction from potassium phosphate buffer followed by FPLC and HPLC steps. Based on amino acid residue, this peptide is amphipathic and basic with one net positive charge having isoelectric pH 8.1. This peptide is without sulphur containing amino acid suggesting its extended conformation lacking doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
0
26
0
2
Order By: Relevance
“…DBT consists of a mixture of benincasa seed, peach kernel, moutan bark, rhei rhizoma, and natrii sulfas. Of these, the antimicrobial activity or anti‐inflammatory potency of rhei rhizoma and benincasa seed have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…DBT consists of a mixture of benincasa seed, peach kernel, moutan bark, rhei rhizoma, and natrii sulfas. Of these, the antimicrobial activity or anti‐inflammatory potency of rhei rhizoma and benincasa seed have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide was 5.7 kDa (49 amino acid residues), basic and amphipathic 129 . It does not comprise of any sulphur containing amino acid, which suggested that it does not have any secondary structure.…”
Section: Mandal Et Al Isolated Cn-amp1 Cn-amp2 Andmentioning
confidence: 98%
“…Estos resultados respaldan la hipótesis de que péptidos activos y proteínas derivadas de plantas tienen efectos beneficiosos en la salud humana, en este caso, en el proceso de cicatrización (7,26) .…”
Section: Referencias Bibliográficasunclassified
“…Además de estos componentes, las plantas son las principales fuentes de péptidos, los cuales son moléculas de proteínas de menos de 10 kDa; que pueden existir de forma natural o ser derivados de secuencias de proteínas nativas (5,6) . En los últimos años, una amplia evidencia científica ha previsto la existencia de péptidos activos biológicos y proteínas derivadas de plantas que podrían tener efectos beneficiosos sobre la salud humana (7) .…”
Section: Introductionunclassified